Advances in clinical genetics and its current challenges - Fernando Santos Simarro (Anales de Pediatría (English Edition), 2022)
The great advances in the development of genomic technologies and their incorporation into routine clinical practice is bringing about a change in which an individual's genetic information is becoming increasingly relevant to their medical care. This is known as genomic medicine. Its implementation is not without barriers, including difficulties in the assessment and interpretation of genomic data, deficient training of professionals and patients in this field, unequal access to units with expertise, and a lack of professional profiles and infrastructures necessary for the incorporation of genomic technologies into routine clinical practice. This article reviews the advances and challenges of genomic medicine. Resumen: Los grandes avances en el desarrollo de las tecnologías genómicas y su incorporación a la práctica clínica habitual, está suponiendo un cambio en el que la información genética de un individuo tiene cada vez mayor relevancia en su atención médica. Esto es lo que se conoce como medicina genómica. Su implementación no está exenta de barreras entre la cuales se encuentran las dificultades en el asesoramiento e interpretación de los datos genómicos, una formación deficiente de los profesionales y los pacientes en este campo, un acceso desigual a unidades con experiencia y una falta de perfiles profesionales e infraestructuras necesarias para la incorporación de las tecnologías genómicas en la práctica clínica habitual. En este artículo se revisan los avances y retos de la medicina genómica.